Land development for civil engineers - Dion, Thomas R.; Dion, Thomas R. (New York : John Wiley & Son, Inc., 1993)
This engineering reference work covers the non-structural aspects of land development. The reader is guided through the stages of an actual development project, beginning with pre-design activities, followed by the design stage and concluding with coverage of the engineer's role in construction.
Developer's constraints -- Engineering administration -- PRELIMINARY ENGINEERING ACTIVITIES -- Inventory, analysis, and reporting -- Preliminary design and costs -- FINAL DESIGN RELATED ACTIVITIES -- Transportation system design -- Drainage system design -- Sedimentation and erosion control -- Site grading and appurtenance design -- Sanitary sewer system design -- Potable water system design -- Miscellaneous design considerations -- Project manual including specifications -- Project costs and scheduling -- Development guidelines -- Completion of design activities -- CONSTRUCTION RELATED ACTIVITIES -- Contracts and award. layout, observation, and monitoring -- Completion and start-up.
Includes index.
Keywords: CIVIL ENGINEERING -- HANDBOOKS, MANUALS, ETC